FORMULASI DAN UJI ANTIBAKTERI EKSTRAK BIJI KETUMBAR (Coriandrum sativum L.) PADA SEDIAAN SPRAY GEL ANTIJERAWAT DENGAN VARIASI CARBOPOL 940 - Muhammad Zielal Askari; Muhammad Nurul Fadel; Bintari Tri Sukoharjanti (Yayasan Nusantara Hasana Berdikari, 2025)
Acne is a skin problem or infection that generally appears on the face, neck, chest, and back. Acne is caused by the bacteria Propionibacterium acnes. Acne treatments that are often used are topical medications containing synthetic antibiotics. However, the use of these drugs can cause adverse resistance. Another alternative for acne therapy is using natural ingredients. This study aims to determine the antibacterial activity of coriander seed extract in a spray gel preparation. Flavonoid, terpenoid, saponin and tannin compounds contained in seeds This study is an experimental laboratory study using the disc diffusion method with 5 treatments, namely coriander seed extract with a concentration of carbopol F1 0.1%, F2 0.2%, F3 0.3%, a positive control spray gel brand